Profits, Layoffs, and Priorities - Arce M., Daniel G.; Li, Sherry Xin (2011)
This study examines the deliberations of professional MBA students when presented with a dilemma that weighs the difference between commitments to profit- maximization against concerns for fired workers who would need to seek a new job during a recession. Using content analysis, accounting, economic, and ethically based rationales that differ from the profit-maximizing recommendation are categorized. Results also show that those who make non-profit-maximizing recommendations consider, but ultimately reject the profit-maximizing approach to layoffs.
Keywords: Unemployment; Self-interest; Recession; Profits; layoffs; Experimental Economics; Downsizing; Content Analysis; Business Ethics; Behavioral economics